2015
DOI: 10.3164/jcbn.15-90
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal molecular hydrogen administration on lipopolysaccharide-induced mouse fetal brain injury

Abstract: Fetal brain injury is often related to prenatal inflammation; however, there is a lack of effective therapy. Recently, molecular hydrogen (H2), a specific antioxidant to hydroxyl radical and peroxynitrite, has been reported to have anti-inflammatory properties. The aim of this study was to investigate whether maternal H2 administration could protect the fetal brain against inflammation. Pregnant C3H/HeN mice received an intraperitoneal injection of lipopolysaccharide (LPS) on gestational day 15.5 and were prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Notably, H 2 was demonstrated to exert anti-oxidative and anti-inflammatory effects in foetal organs following intraperitoneal injection of LPS in rodent models (7)(8)(9). It is established that preterm labour is associated with inflammation, but the associated mechanism is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, H 2 was demonstrated to exert anti-oxidative and anti-inflammatory effects in foetal organs following intraperitoneal injection of LPS in rodent models (7)(8)(9). It is established that preterm labour is associated with inflammation, but the associated mechanism is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous reports demonstrated that may H 2 prevent foetal inflammation and oxidative damage (7)(8)(9), and compared to the effects of H 2 on foetal damage, its effects on preterm labour were limited. These findings suggest that H 2 pretreatment may be appropriate for preventing foetal injury from maternal inflammation at preterm labour, but has low potential to inhibit preterm birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…reported that maternal administration of HW ameliorates mouse fetal brain injury induced with maternal exposure to LPS. Expression of pro-inflammatory cytokines, oxidative damage, and microglial activation caused by intrauterine inflammation are suppressed by HW [ 78 , 79 ]. These data suggest that prenatal administration of H 2 can be an effective therapeutic approach for FIRS.…”
Section: Neonatal Brain Disordersmentioning
confidence: 99%